A Descriptive Analysis of the Characteristics of School Shootings Across Five Decades - Gammell, Sarah P. (American journal of criminal justice, 2022)
Research on understanding school shootings has traditionally focused on the individual level factors surrounding several highly publicized mass shooting events such as those in Parkland, Florida and Santa Fe, Texas. However, researchers have recently begun to examine characteristics among other types of shootings on K-12 school campuses, including non-mass and non-fatal shooting incidents. Correlates such the type of firearms used, the number of firearms, the age of the perpetrator, and school level, have been shown to differentially affect the severity of a school shooting incident. The current study provides a descriptive analysis of shooter, school, and incident level characteristics as they relate to the predicting casualties and fatalities in school shooting incidents from 1970-2020. Results suggest that school and incident characteristics are significantly related to school shooting severity. We discuss the importance of broadening the understanding of school shootings to include these other types of incidents.